A Majority Group's Perspective-taking Towards a Minority Group: Its Antecedents and Impact on Support for Minority Helping. (March 2017) - Mashuri, Ali; Zaduqisti, Esti; Ula, Miftahul
This research investigates the impact of perspective-taking on a majority group's support for government action to help a minority group. Data among a sample of Indonesian Muslims ( N = 380), representing a religious majority group in Indonesia, showed that perspective-taking was a strong positive predictor of Muslims' support for government action to help Christian minority. Relative Muslim prototypicality vis-à-vis Christians depressed perspective-taking. Contrariwise, inclusive victimhood reflecting a perception that Muslims are equally afflicted relative to Christians in intergroup conflicts, involving both groups, promoted perspective-taking. Relative Muslim prototypicality was augmented by the extent to which this majority group glorified Islam and was motivated to protect Islamic power. However, inclusive victimhood instead attenuated relative Muslim prototypicality. These findings suggest the importance of enhancing inclusive victimhood, given its impact in promoting perspective-taking which is beneficial to the majority's support for minority helping.